The Effect of Risk Tolerance, Entrepreneurship Motivation and Self Efficacy on Entrepreneur Intention of University Students - Abdurrahman Sadikin; Ilham Akbar; Samuel PD Anantadjaya; Irma M. Nawangwulan; Ikhsan Amar Jusman (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
This study's objective is to examine and gather empirical information on the relationships between college students' entrepreneurial goals and their motivation, self-efficacy, and risk tolerance. Management students in semesters 6 and 8 participated in this study as respondents. In this case study, 85 management students were selected as a sample. Based on the purposive sampling technique. Multiple linear regression analysis approaches are used to test the hypothesis in this case study. The findings indicated that entrepreneurial desire, self-efficacy, and risk tolerance all had an impact on entrepreneurial intention whereas risk tolerance had no impact. This research demonstrates that entrepreneurial intention is simultaneously influenced by entrepreneurial motivation, self-efficacy, and risk tolerance.